Pengaruh kesadaran moral, citra merek, dan word of mouth terhadap niat pembelian Nintendo switch di Surabaya - Andhika Persada Putra; Emma Yulianti (STIE Perbanas Surabaya, 2018)
Consumers’ intention to purchase is an important factor for the company sustainability. Therefore, each company must pay attention to the factors affecting the consumers’ intention to purchase. This factor can be gained when the consumers are aware, knowing the brand has a good image. This study tries to fi nd out how brand awareness, brand image, and word of mouth affect the customers’ intention to purchase of Nintendo Switch in Surabaya. This study used a quantitative method. The data were collected using questionnaires and 82 respondents was obtained and these data were analyzed using multiple regression. The results showed that brand image and word of mouth signifi cantly affect customers’ intention to purchase while brand awareness dose not for the customers of Nintendo Switch in Surabaya. It implies that the company should pay attention to brand image and word of mouth in order to enhance consumers’ intention to purchase.